Facile and efficient enzymatic methods for harvesting or removal of cuticle cells from human hair shafts - Zhang, Nan (2022)
Human hair fibers are structurally organized as a cortex protected by an outer scaly sheath (cuticle). Developing methods to isolate these two compartments will help to elucidate their roles in hair biology and develop potential applications. Herein, we developed enzymatic methods for human hair cuticle cell harvesting or removal. After a single treatment with esperase for three days, cuticle cells were released from hair shafts and effectively harvested by a series of filtration, centrifugation and resuspension steps. Separately, combining L-cysteine and either esperase or savinase could remove the entire cuticle layer to obtain descaled hair fibers. The physical and chemical structures, and performance of the isolated cuticle cells and descaled hair samples were characterized using electron microscopy, FTIR, solid state 13C NMR, TGA and DSC. Results show that the harvested cuticle cells contain mainly β-sheets and random coil structures, while descaled hair samples contain more α-helical structures. Harvested cuticle cells have greater thermal stability than the descaled hair samples below 260 C. The enzymatic methods developed in this study are convenient and easily controlled. They are effective not just for cuticle cell harvesting but also for surface modification and structure disintegration of hair fibers.